THE SIGNIFICANCE OF NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING THE USE OF SYNONYMS AND VOCABULARY IN THE ENGLISH LANGUAGE (Conference Zone, 2022)
The article scientifically analyzes the importance of new pedagogical technologies in teaching the use and vocabulary of synonyms in the English language. Practice has shown that the process of learning a language is more effective when the class is organized into groups of students. This allows the student to approach groups differently as needed during the lesson, placing more emphasis on repetition and giving additional tasks to the fast learner. The lessons will have a number of educational purposes. the teacher can use a number of exercises to achieve these goals